The Development of Mobile-Based for Online Thesis Guidance - Amnah - Amnah; Indra Budi Sumantoro; Yan Aditiya Pratama (Prosiding International conference on Information Technology and Business (ICITB), 2022)
Nowadays, technology becomes more sophisticated. Especially in mobile technology, it already has various types and operating systems. One that is widely used by the community is Android. During the Covid-19 pandemic, students are difficult to conduct thesis guidance because the teaching and learning process in the university is not required to come. Sometimes, the schedules of did not match or the lecturers are out of town so they cannot do correctly. With mobile technology, thesis guidance can be used online, guidance and mobile. This application was designed for an online guidance support system. Moreover, it helps in solving problems encountered in the tutoring process. Keywords: Guidance, Thesis, Smartphone